Graded Ultra-Translucent Zirconia (5Y-PSZ) for Strength and Functionalities. (October 2018) - Mao, L.; Kaizer, M.R.; Zhao, M.; Guo, B.; Song, Y.F.; Zhang, Y.
Ultra-translucent zirconias are drawing immense attention due to their fascinating esthetic appearance. However, the high translucency came at the expense of diminishing strength along with the reduced ability of transformation toughening due to the increased cubic zirconia content. We aim to address these issues by infiltrating glass on the surface of an ultra-translucent zirconia (5Y-PSZ). Glasses of different shades can be used and the resulting graded glass/zirconia layer is expected to improve the material's flexural strength without compromising its esthetics. We also aim to elucidate how clinically relevant surface treatments—namely, air abrasion, glazing, or polishing—affect the fracture resistance of these zirconias with a high cubic content. All surface treatments were performed on bar-shaped (2 × 3 × 25 mm 3 ) and plate-shaped (12 × 12 × 1 mm 3 ) specimens, which were then subjected to a 4-point bending test and translucency measurements, respectively. 5Y-PSZ proved to be significantly more translucent than 3Y-TZP but also much weaker. Our hypothesis was accepted, as the strength of the glass-infiltrated ultra-translucent 5Y-PSZ (582 ± 20 MPa) is over 70% higher than its uninfiltrated counterpart (324 ± 57 MPa). Its strength is also over 25% higher than the highly polished 5Y-PSZ (467 ± 38 MPa). In addition, the translucency of 5Y-PSZ (translucency parameter [ TP ] = 34, contrast ratio [ CR ] = 0.31) is not affected by glass infiltration ( TP = 34, CR = 0.32) when the residual surface glass is removed by gentle polishing using 6- and then 3-µm diamond grits. Finally, both air abrasion and the presence of a glaze layer on the tensile surface decreased flexural strength significantly, being 274 ± 55 and 211 ± 21 MPa, respectively. With a combined high strength and translucency, the newly developed glass-infiltrated 5Y-PSZ may be considered a suitable material for next-generation, damage-resistant, and esthetic dental restorations.